Marketing de relacionamento em indústrias de bens de consumo de massa: uma relação possível? - Aimola, Veridiana Nogueira (2011)
The vision of this work is based on the urgency of other work and study, developed relationship marketing, bringing the main objective to identify possible constraints to the development or not of relationship marketing in consumer goods industries of mass. To do so, present a literature review on the subject and analyze how companies use relationship marketing as a strategy, are key highlights of this dissertation. Especially within the model of relationship marketing Gummesson, also known as 30 Rs. The elements of performance and proposed strategies are based on experiences gained through the data collection performed on field research conducted in the Unit of Analysis AmBev, the largest private consumer goods in Brazil, located in Sao Paulo, which had the support of ABIR - Brazilian Association of Soft Drinks and Soft Drinks. The methodology is set by the recommendations of Robert Yin, working with a single case study, however, using multiple sources of evidence as the researcher's observation, interviews, institutional materials, as well as research on the internet. Based on the convergence of different theoretical perspectives, the approach taken by this logic is no longer in tangible assets, the value entered or transactions, but on intangible assets such as skills, information and knowledge co-creation of value between them and the client organization and especially relationships. It was found that relationships are emerging as an important component of organizational performance, which is central to understanding the assumptions of a relationship, such as trust and commitment between the parties, the background of the relationship, such as some types of costs change, and, especially, the resulting relationship (eg loyalty). It is extremely complicated and difficult working relationship marketing in an industry of mass consumption. However, social media is emerging as an instrument approach to the public and, therefore, work try to give concreteness to relationship marketing